Metabolome and Transcriptome Analyses of Cucurbitacin Biosynthesis in Luffa (Luffa acutangula) - Zhao, Gangjun; Wang, Meng; Luo, Caixia; Li, Junxing; Gong, Hao; Zheng, Xiaoming; Liu, Xiaoxi; Luo, Jianning; Wu, Haibin (Frontiers in Plant Science, 2022)
Cucurbitacins are extremely bitter compounds mainly present in Cucurbitaceae, where Luffa belongs. However, there is no comprehensive analysis of cucurbitacin biosynthesis in Luffa fruit. Therefore, this study analyzed bitter (WM709) and non-bitter (S1174) genotypes of Luffa to reveal the underlying mechanism of cucurbitacin biosynthesis by integrating metabolome and transcriptome analyses. A total of 422 metabolites were detected, including vitamins, essential amino acids, antioxidants, and antitumor substances. Of these, 131 metabolites showed significant differences between bitter (WM709) and non-bitter (S1174) Luffa fruits. The levels of isocucurbitacin B, cucurbitacin D, 23,24-Dihydro cucurbitacin E, cucurbitacin F were significantly higher in bitter than in non-bitter Luffa. Transcriptome analysis showed that Bi, cytochromes P450s (CYP450s), and acyltransferase (ACT) of the cucurbitacin biosynthesis pathway, were significantly up-regulated. Moreover, drought stress and abscisic acid (ABA) activated genes of the cucurbitacin biosynthesis pathway. Furthermore, dual-luciferase reporter and yeast one-hybrid assays demonstrated that ABA-response element binding factor 1 (AREB1) binds to the Bi promoter to activate Bi expression. Comparative analysis of the Luffa and cucumber genomes showed that Bi, CYP450s, and ACT are located in the conserved syntenic loci, and formed a cucurbitacin biosynthesis cluster. This study provides important insights into major genes and metabolites of the cucurbitacin biosynthetic pathway, deepening the understanding of regulatory mechanisms of cucurbitacin biosynthesis in Luffa.